2012
DOI: 10.4021/cr198e
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Cardiovascular Risk Factors Among University Students: The Gender Factor

Abstract: BackgroundEvidence indicates that the pathophysiological process of cardiovascular (CV) disease begins at early age, though the manifestations of the disease do not appear until middle age adulthood. Risk factors for CV disease, particularly lipoprotein profiles, are affected by physiological abnormalities, and lifestyle related issues. To evaluate prevalence of CV diseases risk factors among university students and to investigate relation between number of risk factors and body anthropometric, hematological a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 31 publications
4
5
0
Order By: Relevance
“…However the differences in proportion of obesity between males and females was not significant here as also observed in other studies. 9,18 Central obesity was seen significantly more among females in this study as also reported in several studies. 9,19,20 On the contrary a Greek study found central obesity significantly more among males.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…However the differences in proportion of obesity between males and females was not significant here as also observed in other studies. 9,18 Central obesity was seen significantly more among females in this study as also reported in several studies. 9,19,20 On the contrary a Greek study found central obesity significantly more among males.…”
Section: Discussionsupporting
confidence: 87%
“…Among these parameters, HDL followed by WC was abnormal among most participants in the present study which was similar to the finding of previous studies. 9,18 Abnormalities with WC followed by HDL levels was also reported by few other studies. 7,22 The indicator of metabolic syndrome that was seen least common among medical students in this study was, elevated TG followed by elevated FBS in comparison to elevated FBS followed by elevated BP reported in the study done in Bangalore, India.…”
Section: Discussionsupporting
confidence: 70%
See 3 more Smart Citations